(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
A 8x8 multiple input multiple output an tenna is developed for the applications of MM wave. this proposed model has 8 ports on the single structure of anten na system. The proposed design gives a triple bands k-band (14.6 at-22dB), ku-band(19.6 at -28dB) and ka-band(27.6 at -27dB) which this ka-band wii be act as mm wave band for the applications of MM wave. The proposed antenna having the dimensions of 64mm x 32mm x 1.6 mm having thick ness 1.6mm and the Fr4 substrate has been used for design ing. The proposed antenna is designed, measured and tested